2006 Workshop on High Performance Switching and Routing 2006
DOI: 10.1109/hpsr.2006.1709673
|View full text |Cite
|
Sign up to set email alerts
|

RFC 2544 performance evaluation and internal measurements for a Linux based open router

Abstract: Recent technological advances give a good chance to do something really effective in the field of open Internet equipments, also called Open Routers (ORs). Some initiatives have been activated since the last few years to investigate the OR and related issues. But despite these activities, large interesting areas still require a deeper investigation. This work tries to give a contribution by reporting the results of an in-depth activity of optimization and testing realized on a PC Open Router architecture based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…Crucially, small storage can only be attained if the leaf-push barrier is chosen according to (2). Strikingly, we found that precisely this setting is the key to fast FIB updates as well 2 .…”
Section: Updatementioning
confidence: 84%
See 1 more Smart Citation
“…Crucially, small storage can only be attained if the leaf-push barrier is chosen according to (2). Strikingly, we found that precisely this setting is the key to fast FIB updates as well 2 .…”
Section: Updatementioning
confidence: 84%
“…If p < λ, then updating a single entry can be done in O(W ) time. If, on the other hand, p ≥ λ, then update visits at most W + 2 W −λ ≤ W + W H 0 nodes, using that λ ≥ W − lg( W H 0 ) whenever λ is as (2). In summary, under mild assumptions on the label distribution a prefix DAG realizes the Shannon-entropy up to a 2 Note that (2) transforms into (1) at maximum entropy.…”
Section: Updatementioning
confidence: 99%
“…Correspondingly, FIBs continue to expand both in size and management burden. As a quick reality check, the Linux kernel's fib_trie data structure [41], when filled with this many prefixes, occupies tens of Mbytes of memory, takes several minutes to download to the forwarding plane, and is still heavily debated to scale to multigigabit speeds [2]. Commercial routers suffer similar troubles, aggravated by the fact that line card hardware is more difficult to upgrade than software routers.…”
Section: Fib Compressionmentioning
confidence: 99%
“…Correspondingly, FIBs tend to grow large both in size and management burden, presenting a crucial bottleneck in the data-plane performance of routers and forcing operators into rapid upgrade cycles [2]. As a quick reality check, the Linux kernel's fib_trie data structure [3], when filled with 400,000 prefixes, occupies more than 20 Mbytes of memory, takes several minutes to download to the forwarding plane, and is still heavily debated to scale to multigigabit speeds [4]. Commercial routers suffer similar troubles, aggravated by the fact that line card memory is much more difficult to upgrade than software routers.…”
Section: Introductionmentioning
confidence: 99%